Investigating Highway-incurred Soil and Plant Lead Contamination in Iran - Istanbuly, Mustafa Nour; Amiri, Bahman Jabarian; Hamidian, Amir Hussein (Journal of natural sciences, life and applied sciences, 2019)
In the framework of the classical environmental impact assessment (EIA) of roads, there is a considerable likelihood that the required attention is not paid to the interactions of environmental impacts. These interactions exist among various factors of the peripheral environment of roads. Applying a multi- factor approach in EIA tasks would provide the practitioners of EIA with a more integrated approach. This approach would help them achieve more reliable findings for decision-making. Accordingly, integrating laboratory findings with computer-based techniques such as geo-statistical analysis would provide the EIA practitioners with the spatial concentration of pollutants. It directs them into more reliable decisions by decreasing the extent of uncertainty in the decision-making process.In the present study, our findings showed that the lead concentration in the plants had an inverse relationship (r = -0.524, p
Keywords: environmental impact assessment; soil; plant; pollution; highways